Digital twinship in heritage buildings and the evolution of this concept in scientific production - Bulgarelli-Bolaños, Jose Pablo (2023)
The aims of this paper are to describe what is meant by “digital twin of patrimonial works” and to present the results of a bibliometric analysis of scientific publications dealing with this concept. These articles were registered in the Elsevier Scopus database, during the period between 2018 and July 2022. This analysis was developed by the research team, from the Costa Rican Technological Institute, of the project: “Digital twin as a management tool of the programmed conservation plan; case study: foyer and smokers of the National Theater of Costa Rica”. This scientific production was carried out prior to the formal start of the execution of the project, to generate a precise contextualization of the topic in question and as input for the development of its objectives. The bibliometric indexes described include authors, time of publication, affiliations, countries with the highest scientific production related to the concept and main research niches. A total of 35 publications were considered, produced by 151 authors, from 66 affiliations, in 21 countries. It was determined that, although the conceptualization of the digital twin of heritage works exists within the scientific production, there are few cases  and, therefore, of the development of the tool.